MODELLING THE EFFECT OF HUMAN ACTIVITIES ON THE NUTRIENT TRANSFER IN THE RED RIVER BASIN (VIETNAM): PRESENT SITUATION AND PROSPECTIVE SCENARIOS FOR THE NEXT 50 YEARS - T. P. Q. Le; J. Garnier; G. Billen; S. Thery; T. T. Duong (Lowland Technology International, 2009)
The Red River (Vietnam and China), which covers a watershed area of 156451 km2 with a total population near 30 million inhabitants, is one of the two largest rivers in Vietnam. The backbone of this work consisted in implementing the Seneque/Riverstrahler software which was successfully applied for the first time to a tropical river system as the Red River for assessing the link between human activity in the watershed and water quality of this river system. The first application of this model to the Red River system is described and validated with the data acquired by the monthly surveys of water quality at the outlet of the 3 sub-basins and in the main branch of the Red River during the years 2003 and 2004. After being validated, the model is used to explore a variety of scenarios describing possible future changes, concerning the hydrological management, population increase and land use and agricultural practices in the Red River basin in the next 50 years. The results show a clear increase of the N/P ratios is predicted for the 2050 scenario with respect to the 2003 situation, along with a clear decrease of the Si/N ratios at the outlet of the Red River.